Baclofen overdose: A curious case of medical sales representative. Issue 8 (9th August 2022) - Gautam, Swotantra; Neupane, Aakash; Chamlagain, Mandita; Pokhrel, Sandip; Neupane, Durga; Acharya, Rochana; Panthi, Sagar
Abstract: In this case report, a medical sales representative consumed 250 mg of Baclofen out of curiosity. Baclofen has life‐threatening complications like seizures, respiratory depression, and coma. A majority of patients recover on symptomatic treatment. Baclofen has a great potential for abuse and overdose; therefore, its use must be strictly monitored. Abstract : Baclofen, commonly used muscle relaxant, carries great risk of abuse and poisoning. Baclofen overdose may cause coma, respiratory depression, and cardiovascular abnormalities in severe cases. The management is mainly symptomatic in an ICU setup with respiratory support. The interventions are tailored to each case as specific antidote is not available.